A flexible and high-performance all-solid-state supercapacitor device based on Ni3S2 nanosheets coated ITO nanowire arrays on carbon fabrics. Issue 79 (9th August 2016) - Yang, Jie; Fang, Chun; Bao, Chunxiong; Yang, Weiwei; Yu, Tao; Zhu, Weidong; Li, Faming; Liu, Jianguo; Zou, Zhigang
Abstract : Ni3 S2 nanosheets coated ITO nanowire arrays on carbon fabrics can achieve an all-solid-state flexible supercapacitor with outstanding capacitive performance. Abstract : A Ni3 S2 coated indium tin oxide (ITO) core–shell structure on flexible carbon fabrics (CF@ITO@Ni3 S2 ) was prepared by electrodepositing Ni3 S2 nanosheets on ITO nanowire arrays grown on flexible carbon fabrics by chemical vapor deposition. The ITO nanowires on carbon fabrics formed a conductive support which offered a large contact surface with the electrolyte and hence was accessible for ion diffusion. Ni3 S2 nanosheets were uniformly deposited on the ITO nanowire. The maximum mass loading of Ni3 S2 on ITO nanowire array coated carbon fabrics could reach about a quadruple higher amount than that on the bare carbon fabrics. The prepared CF@ITO@Ni3 S2 electrodes exhibited excellent capacitive performance compared with Ni3 S2 coated bare carbon fabric electrodes (CF@Ni3 S2 ). High areal capacitance of 3.85 F cm −2 and gravimetric capacitance of 1865 F g −1 were achieved when the mass loadings of Ni3 S2 on the ITO nanowire arrays were around 4.12 mg cm −2 and 0.96 mg cm −2, respectively. The sample with 0.96 mg cm −2 of Ni3 S2 could also deliver 1372 F g −1 when charge–discharge current density reached 50 mA cm −2, indicating the excellent rate capability of the structure. The assembled all-solid-state full cell based on symmetric electrodes obtained a relatively high areal capacitance of 736 mF cm −2 at 8 mA cm −2, which delivered a maximum energy density of 1.02 mW h cm −3 at a power density of 39.9 W cm −3 . The outstanding capacitive performance suggests that the CF@ITO@Ni3 S2 device was promising for application in an inexpensive energy storage system.